Uma poética entre a transensorialidade e a correspondência (Significação: Journal of Audiovisual Culture, 2010)
VJing and live A/V practices are an expression of the intersection of the senses, such as sight and hearing. The images, which are manipulated live establish temporalities by the evolution of forms. The figuration of communication icons attempt to resist and this happens, not necessarily in terms of an image’s visibility, but in the sequential principle of fixed and moving images. There is a primacy of the motion and visual excitement over a continuous length of time. We centralize the discussion on the tendency to visual and sensitive abstractionism as one of the fingerprints of the creation on a dance floor. We will see how this poetics, which prioritizes the aesthetics of the suggestion. These projections promote a space-time continuum and evoke more than one sense as aesthetic experience.